Designing Science Learning Domains for 2e (Twice Exceptional) Students - Ümmüye Nur Tüzün (Universitas Pendidikan Indonesia, 2021)
2e (twice-exceptional) students are gifted and differently-abled, so they need specific learning domains according to their needs. This research aimed to design science learning domains for a 2e (gifted and blind) student to enhance his critical thinking in his special learning needs in Ankara province in Turkey in the 2020-2021 academic year's first term. Single-subject research was employed. The 2e student was ten years old. Through the application process, the 2e student argued 3D modeled Schrödinger's cat thought experiment. The main application's intervention was conducted to provide the research's internal validity since it was single-subject research. Through the intervention application, the 2e student argued 3D modeled Schrödinger's twin cats thought experiment. We noted both social dialectic argumentation processes as texts, and these texts were used as data collecting tools. Descriptive analysis was utilized to gathered data. The study showed that the 2e student could construct arguments containing claim, data, warrant, and weak rebuttals in the main application, which meant his argumentation quality level was average, so his critical thinking too. In contrast, the 2e student-constructed arguments containing claim, data, weak rebuttal, and rebuttal meant his argumentation quality level enhanced his critical thinking.